Blaming Islam - Bowen, John Richard 1 951- (Boston review book, 2012)
In Blaming Islam, John Bowen uncovers the myths about Islam and Muslim integration into Western society, with a focus on the histories, policy, and rhetoric associated with Muslim immigration in Europe, the British experiment with sharia law for Muslim domestic disputes, and the claims of European and American writers that Islam threatens the West. Most important, he shows how exaggerated fears about Muslims misread history, misunderstand multiculturalism's aims, and reveal the opportunism of right wing parties who draw populist support by blaming Islam